Drug utilization pattern and physician adherence to treatment guidelines in inpatients with urinary tract infection - Sharma, Ajitha; Oommen, Shweta (International Journal of Basic & Clinical Pharmacology, 2018)
Background: Mainstay of management in urinary tract infection (UTI) is antibiotics and it is seen in recent years that antibiotic resistance is increasing. However, very few treatment guidelines exist for UTI and often treating physicians may not adhere to these guidelines. Aims: Current study was undertaken to analyze antimicrobial prescription pattern and utilization, and check for physician adherence to treatment guidelines in UTI. Methods: This retrospective, record-based study was carried out in a tertiary care hospital in inpatients with UTI. Tabulated data was analyzed using WHO core drug prescribing indicators and Anatomical Therapeutic Chemical/ Defined Daily Dose (ATC/DDD) index. Adherence to treatment guidelines was assessed using Indian Standard Treatment Guidelines for Urology. Data documented in SPSS software was analyzed using χ2-test and multinomial logistic regression. Results: Among 364 patients included in study, equal incidence of UTI was seen in both sexes (male to female ratio 1.02:1). Prolonged hospital stay (>7 days) was associated with elderly age group (OR=3.09, CI95% 1.83-5.21), complicated UTI (OR=8.11, CI95% 4.62-14.24), ESBL-producing E. coli (OR=3.07, CI95% 1.58-5.94), non-adherence to treatment guidelines (OR=8.65, CI95% 4.19-17.84), and presence of comorbid conditions like diabetes mellitus (OR=4.89, CI95% 3.05-7.82), benign prostatic hypertrophy (OR=2.76, CI95% 1.36-5.59) and utero-vaginal prolapse (OR=8.33, CI95% 2.28-30.45). Average number of drugs prescribed per encounter was 1.59, while drugs prescribed by generic name and from essential drug list were 98.1% and 70.69% respectively. Majority of prescriptions (87.6%) adhered to standard treatment guidelines. Prescribed daily dose (PDD) and defined daily dose (DDD) were equal for most antibiotics prescribed. Conclusions: Majority of prescriptions were adhering to treatment guidelines but the need to prescribe using generic name and from essential drug list should be emphasised upon.